Transnational Sufi Networks in India and Anatolia: Naqshbandiyah-Mujaddidiyah Order - Kutlutürk, Cemil (Journal of History Culture and Art Research, 2020)
India and Turkey, noticeable for their strong historical background and geopolitical importance, have left their mark on the history of humanity via their outstanding wise men and a vibrant cultural and religious heritage. Even though political and military relations have occurred between these two regions, it should be stated that one of the most energetic interactions between them has taken place in the area of religion and culture, particularly at the core of Sufism. As in the example of the Naqshbandiyah-Mujaddidiyah tradition, some Sufi orders originally flourishing in India have entered into Anatolia through various channels and have taken deep roots there through the eminent Sufi leaders and their efficient endeavors such as training disciples, writing or translating celebrated sources and inaugurating lodges in different centers. Therefore, this paper tries to depict how the Sufi networks have built a transnational connection between the Indian subcontinent and Anatolia and examines the role of cultural perceptions, historical memories, and social fabrics on the evolution of Sufi thoughts, focusing on the sample of the Mujaddidiyah, sub-branch of Naqshbandiyah.